Strain mapping using compressed sensing accelerated 4D flow MRI—Potential for detecting coactivation in thigh muscles - Sinha, Usha; Maldonado, David; Malis, Vadim; Jin, Ning; Smitaman, Edward; Sanchez, Ramon; Chung, Christine; Sinha, Shantanu (Frontiers in Physiology, 2025)
IntroductionDeterioration in knee extensor function is significantly related to decline in functional mobility, stability and proprioception increasing risk of injury and falls. Coactivation of the hamstrings has been reported in normal and neuromuscular conditions during knee extension emphasizing coordinated muscle activation through range of motion. This study evaluated a prototype compressed sensing accelerated 4D Flow (CS-4DFlow) sequence for volumetric MRI strain mapping of the entire thigh during isometric contraction.MethodsDynamic imaging (at 30% and 45% Maximum Voluntary Contraction (MVC)) was performed with the CS-4DFlow sequence integrating a L1-regularized wavelet-based compressed sensing reconstruction. Strain tensors were computed from displacements tracked from the velocity data. % MVC and muscle related differences (within hamstring and quadriceps and between muscle groups) in normal, shear and volumetric strain were statistically analyzed.ResultsTransverse asymmetry of deformation was seen in all the thigh muscles during isometric contraction. Significant differences in the strain indices with %MVC was seen in the quadriceps but not in the hamstrings. The averaged values of the quadriceps and hamstring muscles showed significant differences between the two muscle groups and with %MVC in all the strain indices. Hamstring strain was around 50% of the quadriceps strain signifying a high level of coactivation. Coactivation was also visually confirmed by comparing the directions of the contractile strain and fibers in the two muscle groups.DiscussionThe current study establishes the feasibility of volumetric strain imaging of the thigh under isometric contraction. The ability to map all muscles allows evaluation of coactivation of the hamstrings with potential for application to conditions such as osteoarthritis and ACL deficiency.